Casing failure mechanism during volume fracturing: A case study of shale gas well. (August 2017) - Lin, Tiejun; Yu, Hao; Lian, Zhanghua; Sun, Biao
A large number of casing failures occur during the volume fracturing operation of shale gas, making normal completion stimulations impossible. To solve this problem, rock mechanical experiments and numerical simulation experiments are carried out in this article. It is found that the macroscopic rock mechanical strength reduces most when the crack angle of fissured rock in Longmaxi Formation is 45°, and it reduces stably when the number of cracks increases to 8. The elasticity modulus ratio, yield strength ratio, and compressive strength ratio are 0.70, 0.71, and 0.68, respectively, based on which this article establishes the finite element model for shale gas well X201. Then, the secondary development realizes the dynamic adjustment of the rock mechanical properties during the fracturing. The correctness of method and model in the article is verified through comparing the simulated calculation of casing deformation and the field multi-arm caliper logging data. The casing failure mechanism is revealed, providing a theoretical basis for the prevention of casing failure caused by shale gas fracturing.